The benefits of influenza vaccine in pregnancy for the fetus and the infant younger than six months of age - MacDonald, Noni E (Paediatr Child Health, 2014)
Influenza is a serious problem for infants <6 months of age, whose hospitalization rates for influenza and associated illness are comparable with rates in the elderly. Because influenza vaccines are not effective in this age group, the optimal evidence-based strategy is to administer trivalent inactivated influenza vaccines during pregnancy. Immunizing with trivalent inactivated influenza vaccines in the second and third trimester is well studied and safe, not only providing protection for the pregnant woman and her infant <6 months of age, but also for the fetus by decreasing the risk for low birth weight.